Reproductive pattern of the anchovy, Engraulis encrasicolus (Linnaeus, 1758), in the Boka Kotorska Bay (Montenegro, southern Adriatic Sea) - Đurović, Mirko (Array, 2018)
The annual alteration of gonad morphology in anchovy, Engraulis encrasicolus (Linnaeus,1758), caught in the period from July 2006 to June 2007 using beach seines in the region of Boka Kotorska Bay (Montenegro, southern Adriatic) was studied. Samples were taken each month. Total length of individuals ranged from 6.6 to 12.2 cm, while weight ranged from 1.58 to 11.27 g, Their ovaries were extracted and weighed, and a piece of female gonad tissue was sampled for histological analysis. The length–weight relationship of all anchovy specimens was described by the equation: \(W = 0.0032\) \(L_T 3.2537; (r 2 = 0.9528)\). The lowest GSI values were found in November and remained at low levels until April, which corresponded to the gonad rest stage. The GSI increased gradually during April and May, which coincides with the begining of spawning period. Although primary oocytes (stage I) were present during all months, their percentage increased from October and was the highest during the winter months (November-March 100%). Mature cells, stage IV, were present during April – October period, with highest value in May when they comprised 12.3% of total oocyte number. An increase in the percentage of oocytes in the yolk vesicle (II) and yolk (III) stages occurred in April, remaining almost unchanged until October. Smallest average oocyte size was noticed in period November – February with an average of 59.69 μm, while greatest size was recorded in April 2007, 185.84 μm.